2021
DOI: 10.3390/jpm11030170
|View full text |Cite
|
Sign up to set email alerts
|

Early Warning Scores in Patients with Suspected COVID-19 Infection in Emergency Departments

Abstract: Early warning scores (EWSs) help prevent and recognize and thereby act as the first signs of clinical and physiological deterioration. The objective of this study is to evaluate different EWSs (National Early Warning Score 2 (NEWS2), quick sequential organ failure assessment score (qSOFA), Modified Rapid Emergency Medicine Score (MREMS) and Rapid Acute Physiology Score (RAPS)) to predict mortality within the first 48 h in patients suspected to have Coronavirus disease 2019 (COVID-19). We conducted a retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
8

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 52 publications
1
23
0
8
Order By: Relevance
“… 8 Martín-Rodriguez et al observed that the NEWS2 at hospital admission was the scale with the best capacity to predict early mortality (less than 48 hrs after hospital admission). 12 Su et al found an AUROC of 0.89 (IC95% 0.82–0.96) for NEWS-C score predicting deterioration of the respiratory function and need of intensive respiratory support. 4 Socio et al and Hai Hu et al reported an AUROC of 0.87 and 0.81 respectively for NEWS2 score to predict death at hospital admission.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Martín-Rodriguez et al observed that the NEWS2 at hospital admission was the scale with the best capacity to predict early mortality (less than 48 hrs after hospital admission). 12 Su et al found an AUROC of 0.89 (IC95% 0.82–0.96) for NEWS-C score predicting deterioration of the respiratory function and need of intensive respiratory support. 4 Socio et al and Hai Hu et al reported an AUROC of 0.87 and 0.81 respectively for NEWS2 score to predict death at hospital admission.…”
Section: Discussionmentioning
confidence: 99%
“…National Early Warning Score (NEWS) (1,2,3,4,19,20,21,24,25) FC * , FR € , PAS § , T ∑ , SaO2 £ , uso del dispositivo de oxígeno y nivel de conciencia. National Early Warning Score 2 (NEWS2) (15,16,17,18,19,20,21,22) FC * , FR € , PAS § , T ∑ , SaO2 £ , nivel de conciencia y el uso de oxígeno auxiliar, y una evaluación específica para los pacientes con insuficiencia respiratoria hipercápnica. Quick Sepsis Related Organ Failure Assessment (qSOFA) (2,15,16,18,19,20,22,24,25) FR € , PAS § y nivel de conciencia Modified Early Warning Score (MEWS) (4,14,20,24,27,29,30) FC * , FR € , PAS § , T ∑ y nivel de conciencia Rapid Emergency Medicine Score (REMS) (2,4,19) FC * , FR € , PAS § , SaO2 £ , edad y nivel de conciencia.…”
Section: Instrumento Parámetros De Evaluaciónunclassified
“…Patients must therefore be frequently assessed in terms of intensive care unit (ICU) requirements. Several scoring systems for evaluating severity of disease 2,3 and a number of thoracic computed tomography (CT) algorithms for assessing pulmonary involvement 4 have been developed. However, CT is not suitable for repeated use since it requires the patient to be moved to other areas and involves exposure to radiation 5 .…”
Section: Introductionmentioning
confidence: 99%